The Impact of Governance and Foreign Direct Investment on Economic Growth in Escwa Countries during (1995-2021)- using ARDL Model (Panel Data) (The Arab Journal of Administration, 2026)
The recent period has watched an increasing interest in governance, especially with most countries wants to raise its rates of economic development. Indeed, governance has become a basic condition for achieving development in its sustainable sense, and the role of foreign direct investment in financing the development process remains the focus of attention of many global countries in general and ESCWA countries in particular. Specifically, the study answered a basic question, which is: Is there an impact of both governance and foreign direct investment on the economic growth rate in ESCWA countries during the period (1995-2021), and by using the autoregressive distributed lag (ARDL) model? The study concluded that there is A positive effect of a number of governance indicators on the economic growth rate of ESCWA countries using the Dana panel for the group of twenty ESCWA countries, as the gross domestic product is positively affected by the quality of government, the quality of regulations and legislation, freedom to vote and question, political stability and distance from violence, while this effect was negative for corruption, and the rule of law. When addressing the impact of governance on foreign direct investment using the cointegration test, the study showed that foreign direct investment is negatively affected by corruption, voting, and freedom of accountability, while it is positively associated with the rest of the governance indicators.